Navigating the Multidimensional Impact of Living with Hidradenitis Suppurativa: An In-Depth Netnographic Study on Social Media Platforms - Ericles Andrei Bellei; André Vicente Esteves de Carvalho; Beatriz Magalhães Eng; Carla Tozato; Danilo Hamilko de Barros; Erika Yumi Tamashiro; Gleison Vieira Duarte; Rafael Toledo Rodrigues de Fátima; Renata Ferreira Magalhães; Roberto Souto da Silva; Wagner Guimarães Galvão Cesar; Felipe Garutti Thies (Adis, Springer Healthcare, 2023)
Abstract Introduction Hidradenitis suppurativa (HS) is a chronic skin condition causing considerable distress. It impacts mobility, social interaction, and quality of life. In Brazil, there is a notable gap in epidemiological data and patient experiences regarding HS. Methods This study, spanning 2019 to 2022, employed netnography to probe the experiences of Brazilian patients with HS. This approach gleans insights from online interactions, offering a direct view into patients' lives. Results Notably, the data illuminated the challenges patients face, such as difficulties in obtaining a diagnosis and the complexities involved in managing a chronic, and often debilitating, condition. Furthermore, patients' experiences with various treatments, encompassing antibiotics, biologic agents, lifestyle alterations, surgical procedures, and alternative remedies, were also examined. Conclusion By undertaking a longitudinal analysis of patient interactions, the study aimed to offer a richer understanding of HS, from its diagnosis to its treatment. It underscores the necessity for a more patient-centered approach when managing this condition. We hope that this enhanced understanding can facilitate better care for those affected by HS.